4+5x=x+23

Simple and best practice solution for 4+5x=x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+5x=x+23 equation:


Simplifying
4 + 5x = x + 23

Reorder the terms:
4 + 5x = 23 + x

Solving
4 + 5x = 23 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
4 + 5x + -1x = 23 + x + -1x

Combine like terms: 5x + -1x = 4x
4 + 4x = 23 + x + -1x

Combine like terms: x + -1x = 0
4 + 4x = 23 + 0
4 + 4x = 23

Add '-4' to each side of the equation.
4 + -4 + 4x = 23 + -4

Combine like terms: 4 + -4 = 0
0 + 4x = 23 + -4
4x = 23 + -4

Combine like terms: 23 + -4 = 19
4x = 19

Divide each side by '4'.
x = 4.75

Simplifying
x = 4.75

See similar equations:

| t+28=13 | | a+5a=2a+a | | -6-3=3x+6-6 | | 1y-2=.33(y+6) | | 9=9-8h | | 5x-1y=15 | | 48+4y-18=14y-12-4y | | X+24=32X | | 3a^2+9a+12=0 | | 4k+8-6k= | | x+x=6+2 | | r(r+3)=0 | | 2y=82 | | 3a^2+9a-12=0 | | 1963-5x=1863 | | n+6/21=4/7 | | 3x+1(-2x+9)=7 | | 36-2(6-2x)=-16 | | n+15=3l | | n/11=40/55 | | 4(20x+15)=1180 | | 4t+7-1=19 | | 8(-9)-(-17)= | | -5=x-2 | | .07*(6000-x)=360 | | 9+4x-2=-15 | | X-1-31=4 | | 3(2x+5)-6(x+2)= | | -2m+13=2-3 | | 15+7(2-4x)=-35 | | 4x+14=60 | | .07*(10000-x)=900 |

Equations solver categories